Implementation of Medical Device Logistics Management: A Qualitative Study - Nur Mila Sari; Widy Try Windy; Nurul Evriany; Indra Eka Wardana Toii (Science Tech Group, 2026)
The total expenditure on medical devices in 2016 was IDR 16.9 trillion from the total health budget in Indonesia. The main problems were the accessibility and quality of medical devices. Good logistics management of medical devices at the Public Health Center (PHC) will affect the quality and financing of health services. This research to find out logistics management of medical devices in Palu City Health Office. The method used Qualitative with case studies. In January-March 2017 in Palu City Health Office. The primary data was obtained through observation, in-depth interviews, and document review. The finding in this research are Palu City Health Office conducted bottom-up planning. However, the allocated budget was limited. Sources of funds were taken from the state budget (APBN) and local government budget (APBD). There was an involvement of official institutions and partners in the procurement of devices. The method of procurement was a tender and direct appointment that referred to e-catalog. But, the items would be available after a long wait. Misunderstanding of information occurred when distributing medical devices in the PHC. There was no special warehouse that was suitable for storing medical devices. The control process in the form of recording and reporting was experiencing errors. Logistics management of health device has not been carried out effectively and efficiently. Thus, it’s necessary to improve optimal coordination and commitment in logistics management of medical devices. This study aligns with SDG 3 (Good Health and Well-being), particularly Target 3.8 on universal health coverage and Target 3.b on access to quality health technologies. Findings also connect to SDG 9 (resilient health infrastructure) and SDG 12 (efficient resource use). Although data were collected in 2017, the structural challenges identified remain pertinent to ongoing health system strengthening in Indonesia and comparable settings.